Disciplinærretlig skyld og straf i danske fængsler - Hans Jørgen Engbo (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article describes disciplinary sanctions applied to imates in Danish prisons. The aricle begins with an explanation of the purpose of disciplinary punishment and of the legal basis for its use. The article then provides an analysis of administrative practices illustrated by descriptions of a few representative disciplinary cases decided by the prisons and appelate cases decided by the courts and the Department of Prisons and Probation. In relation to legal bases, the analysis reveals significant shortcomings regarding both the provision and the assessment of evidence as well as the choice of sanction. The article concludes with a series of recommendations to the authorities.